Performance parameters of ETICS - Parracha, João Luís (2022)
Portuguese Foundation for Science and Technology (FCT) within research project PTDC/ECI-EGC/30681/2017 (WGB_Shield – Shielding building’ façades on cities revitalization. Triple resistance for water, graffiti and biocolonization of external thermal insulation systems). The authors also acknowledge Saint-Gobain Weber, CIN and Secil for the materials supply.